Теплообмін з поверхнями огороджуючих конструкцій плоскої та циліндричної форми - Мартиняк-Андрушко, Марта Андріївна; Мисак, Йосиф Степанович; Гумницький, Ярослав Михайлович (НТУ "ХПІ", 2017)
Для вивчення особливостей процесів теплообміну з поверхнями огороджуючих конструкцій плоскої та циліндричної форми розроблено математичну модель, яка дозволяє штучно відтворювати зовнішні і внутрішні параметри системи. Запропоновану модель можна застосовувати з метою прогнозування оптимальних режимів роботи системи теплопостачання, режимів її експлуатації та вибору схем підключення системи. Модель теплообміну моделює стаціонарні та нестаціонарні умови теплоперенесення. Нестаціонарні умови виникають через добові зміни температури у навколишньому середовищі, яка апроксимована лінійною залежністю зміни температури з часом. Описано процес теплоперенесення для плоскої та циліндричної стінок.

Today, the modes of the release of heat energy by functioning systems are not flexible enough and give no way to the maneuvering; these fail to take into account different external factors that influence their operation. To study the specific features of thermal conditions in the premises European and some domestic researchers develop full-scale physical models to artificially simulate external and internal thermal conditions and the special software, however all these methods require the development of appropriate mathematical models. Experimental investigations are efficient, though cost-based and the obtained data reflect just a certain model in laboratory conditions, therefore we had to investigate thermal conditions at changing ambient temperatures and that required performing a preliminary theoretical simulation. A mathematical model was developed to study the specific features of heat-exchange process with the surfaces of envelop structures of flat and cylindrical shapes. The mathematical model was suggested whose task was to measure the temperature of external envelopes and the environmental heat loss provided that the air temperature inside the facility (the room) was constant, depending on the range of external factors and first of all a change in the ambient temperature T = f, taking into consideration the operation of heating systems. The model suggested can be used for the investigation of the heat-mass exchange, and comfortable conditions for various structures and facilities with different heating systems.
Heat exchange with the surfaces of envelope structures of flat and cylindrical shapes
Keywords: теплопередача; огородження зовнішні; умови нестаціонарні; heat transfer; external envelopes; transient conditions